2021
DOI: 10.1007/978-3-030-92062-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Linearization Attacks

Abstract: Recent works have shown that quantum period-finding can be used to break many popular constructions (some block ciphers such as Even-Mansour, multiple MACs and AEs. . . ) in the superposition query model. So far, all the constructions broken exhibited a strong algebraic structure, which enables to craft a periodic function of a single input block. Recovering the secret period allows to recover a key, distinguish, break the confidentiality or authenticity of these modes. In this paper, we introduce the quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 56 publications
(94 reference statements)
0
13
0
1
Order By: Relevance
“…1 , x 22 2 , x, 𝛼 b ) (See Figure 5). For the 17-round CAST-256, we have 39 1 (𝛼 0 ) ⊕ x 39 1 (𝛼 1 ) ⊕ 𝛼 0 ⊕ 𝛼 1 = x 36 2 (𝛼 0 ) ⊕ x 36 2 (𝛼 1 ) ⊕ 𝛼 0 ⊕ 𝛼 1 (28) where x 39 1 = x 38 4 = x 37 3 = x 36 2 (See Figure 5).…”
Section: Quantum Attack On Round-reduced Cast-256 Block Cipher In Qcp...mentioning
confidence: 99%
“…1 , x 22 2 , x, 𝛼 b ) (See Figure 5). For the 17-round CAST-256, we have 39 1 (𝛼 0 ) ⊕ x 39 1 (𝛼 1 ) ⊕ 𝛼 0 ⊕ 𝛼 1 = x 36 2 (𝛼 0 ) ⊕ x 36 2 (𝛼 1 ) ⊕ 𝛼 0 ⊕ 𝛼 1 (28) where x 39 1 = x 38 4 = x 37 3 = x 36 2 (See Figure 5).…”
Section: Quantum Attack On Round-reduced Cast-256 Block Cipher In Qcp...mentioning
confidence: 99%
“…We believe that it is of theoretical and practical interest to study in more generality, which classes of f admit a memory-efficient computation of their hashed versions. Recently, a first explicit application of our hashed Shor algorithm was given by Bonnetain, Leurent, Naya-Plasencia and Schrottenloher [BLNS21] for the MAC Poly1305.…”
Section: Simon's Algorithmmentioning
confidence: 99%
“…Later on, it was shown that such superposition attacks can target many constructions that are known to be classically secure [67], using Simon's algorithm, but also Kuperberg's algorithm [78] and even Shor's algorithm itself [79]. The practical implications of these attacks remain debated, since without superposition queries, they are inapplicable.…”
Section: Symmetric Cryptographymentioning
confidence: 99%